Strand-specific deep sequencing of the transcriptome - Vivancos, Ana P.; Güell, Marc; Dohm, Juliane C.; Serrano, Luis; Himmelbauer, Heinz

(untitled) (Genome Research, 2010)
Several studies support that antisense-mediated regulation may affect a large proportion of genes. Using the Illumina next-generation sequencing platform, we developed DSSS (direct strand specific sequencing), a strand-specific protocol for transcriptome sequencing. We tested DSSS with RNA from two samples, prokaryotic (Mycoplasma pneumoniae) as well as eukaryotic (Mus musculus), and obtained data containing strand-specific information, using single-read and paired-end sequencing. We validated our results by comparison with a strand-specific tiling array data set for strain M129 of the simple prokaryote M. pneumoniae, and by quantitative PCR (qPCR). The results of DSSS were very well supported by the results from tiling arrays and qPCR. Moreover, DSSS provided higher dynamic range and single-base resolution, thus enabling efficient antisense detection and the precise mapping of transcription start sites and untranslated regions. DSSS data for mouse confirmed strand specificity of the protocol and the general applicability of the approach to studying eukaryotic transcription. We propose DSSS as a simple and efficient strategy for strand-specific transcriptome sequencing and as a tool for genome annotation exploiting the increased read lengths that next-generation sequencing technology now is capable to deliver.